2017
DOI: 10.1016/j.ajog.2016.11.1053
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intrauterine devices on acquisition and clearance of human papillomavirus

Abstract: Background Previous studies have shown a decrease in cervical cancer associated with intrauterine device use. It has been hypothesized that intrauterine device use may alter the natural history of human papillomavirus infections, preempting development of precancerous lesions of the cervix and cervical cancer, but the effect of intrauterine devices on the natural history of human papillomavirus infection and subsequent development of cervical cancer is poorly understood. Objective The purpose of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Previous meta-analyses have demonstrated that the use of an IUD was protective for cervical cancer compared with never using an IUD [ 27 , 28 ]. Furthermore, current IUD use has not been associated with the acquisition or persistence of an HPV infection [ 29 ]. However, a study from the US found significant association of CIN2+ with hormonal IUD use in the past 18 months, while the risk of CIN3+ was not increased [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analyses have demonstrated that the use of an IUD was protective for cervical cancer compared with never using an IUD [ 27 , 28 ]. Furthermore, current IUD use has not been associated with the acquisition or persistence of an HPV infection [ 29 ]. However, a study from the US found significant association of CIN2+ with hormonal IUD use in the past 18 months, while the risk of CIN3+ was not increased [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is no association between non-hormonal contraception used and HPV infection from current study. Besides, previous study had reported that used of non-hormonal method such as IUD has protective association with HPV infection by producing immune mediators that would clear the infection (47).…”
Section: Discussionmentioning
confidence: 99%